EDUKASI DAN PENDAMPINGAN GIZI PADA IBU ANAK BADUTA DAN BALITA GIZI KURANG DI KELURAHAN SUKODONO KECAMATAN GRESIK - Nur Habibatus Sholihah; Nur Qomaria; Rahma Fidania Dwik Nuraini; Yasirotul Hikmah; Amalia Rahma (Universitas Muhammadiyah Gresik, 2022)
Indonesia is a country with various nutritional problems and requires serious handling. This nutritional problem will certainly affect human resources (HR). Problems that are quite high in under-fives and toddlers are short (stunting) and thin (wasting). This activity aims to improve and increase the knowledge of mothers of children aged under two and under five as well as to achieve and improve normal nutritional status in the working area of ​​the Fisherman's Health Center, precisely in Sukodono Village, Gresik District, Gresik Regency. Data collection was carried out in Sukodono Village, Gresik District, Gresik Regency, it was found that 2 respondents were undernourished which was a recommendation from nutritionists at the Fisherman and Cadre Health Center in Sukodono Village. The result of this activity is that there is an increase in the level of knowledge before and after counseling. This is due to the provision of information and education to respondents so that their knowledge increases from those who do not understand to become more aware and from those who do not know to know. In addition, there was an increase in respondents' understanding regarding the intake consumed must be nutritionally balanced and there was a change in the respondent's intake from before counseling to after counseling. There was an increase in weight and height of under-fives and toddlers before and after being given education.